Dependable keyed data entry for interactive systems - Thimbleby, Harold; Gimblett, Andy (Electronic Communications of the EASST, 2011)
Keyed data entry is fundamental and ubiquitous, occurring when filling data fields in web forms, entering burglar alarm pass-codes, using calculators, entering drug delivery rates in infusion pumps, making cash withdrawals from cash machines, setting destinations for GPS navigation, to name but a few of its applications. Unfortunately data entry is often implemented poorly.We introduce divergence, a loss of predictability in a user interface, and show that it is in general unavoidable in data entry, and therefore a systematic approach is called for. This paper presents one such an approach. Many inter-related ideas ``fall into place''---e.g., autocompletion, prompting, automatic color coding---through the approach. The approach contrasts with conventional systems that are generally inconsistent and unhelpful to users, particularly after errors.